Variabel-variabel yang Memengaruhi Deindustrialisasi - Laily Nur Indah Sari; Luci Wulansari (Seminar Nasional Official Statistics, 2022)
The manufacturing industry sector is stated as an engine of growth in supporting the economy of a region. However, in reality there has been a deindustrialization phenomenon or a decrease in the contribution of the manufacturing industry sector to GRDP in industrial areas located outside Java. The phenomenon of deindustrialization is not something that should be ignored considering the important role of industrial estates in both the national and regional economy. Therefore, this study aims to analyze the variables that influence the deindustrialization. The results of the study using panel data regression showed that income per capita, trade balance, and average length of schooling had a significant effect on the contribution of the manufacturing industry sector, while foreign and domestic investment had no significant effect on the contribution of the manufacturing industry sector. In addition, in line with the increase in per capita income with an increase in the contribution of the manufacturing industry sector, it indicates that the type of deindustrialization experienced by industrial estates outside Java is premature deindustrialization.